Effects of edible coatings on the quality and storage of early harvested guava - Formiga, Anderson S. [UNESP]; Pereira, Emmanuel M. [UNESP]; Junior, José S. Pinzetta [UNESP]; Costa, Franciscleudo B.; Mattiuz, Ben-Hur [UNESP] (Elsevier, 2022)
Guava is a world-renowned fruit of climacteric nature. It is characterized as a perishable fruit and has a short post-harvest shelf life when stored at room temperature. The objective of this work is to study the effects of coatings on the physiology and shelf life of 'Pedro Sato' guavas harvested early. For this, the effect of edible coatings based on hydroxypropyl methylcellulose (HPMC) and beeswax (BW) applied to guavas harvested green and stored for eight days at 22 °C was evaluated. Guavas were coated with HPMC+10% BW; HPMC+20% BW; HPMC+40% BW and Control-uncoated. The coatings reduced the respiration rate, inhibited ethylene synthesis and slowed the ripening process. The main benefits were the reduction in mass loss, maintenance of green color and firmness retention. The treatment with HPMC+20% BW presented the best results in maintaining the quality of the fruits, reducing the activity of the PG enzyme and delaying the ripening of 'Pedro Sato' guavas without promoting the activity of the ADH enzyme and consequently the fermentation of the fruits. fruits. The fruits treated with HPMC+20% CA showed a gain in shelf life of at least six days and despite being harvested green, no disorder affected the ripening process and its quality.
Keywords: Beeswax; Biopolymer; Hydroxypropyl methylcellulose; Postharvest; Psidium guajava L